Study on improvement in logistics industry in Gangwon province: Focusing on Yangyang International Airport - Woo Chul Ahn (Asian Journal of Shipping and Logistics (AJSL), 2023)
This study aims to contribute to analyze the logistics competitiveness of Yangyang International Airport and suggest improvement plans for airport logistics experts to use them as basic data to discover the actual factors for revitalizing the Gangwon-do logistics industry. Therefore, the importance and performance level of airport logistics competitiveness factors were investigated and differences were analyzed. The result shows "location", "local cargo demand", " specialized cargo supra-structure", and "government support policy" were surveyed as "focus" areas with high importance awareness but low performance.
Keywords: 650; Fan-Eastsea Region; Hub Airport; Importance Performance Analysis; Low Cost Carrier; Yangyang International Airport